2020
DOI: 10.1111/grs.12279
|View full text |Cite
|
Sign up to set email alerts
|

The optimum seeding and harvesting dates of sorghum–sudangrass hybrid (Sorghum bicolor L.) via optimum moving response surface methodology

Abstract: In general, determining suitable seeding and harvesting times is important in achieving high yields of forage crops in terms of both physiology and ecology. To determine the optimum point, the response surface methodology (RSM) is well known in agricultural science. This study aimed to establish optimum seeding and harvesting dates and to verify the variation of dry matter yield (DMY) for sorghum–sudangrass hybrid (SSH), by determining what we called the “optimum moving RSM” proposed to optimize the RSM in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Test site effect within the central region were also considered as a random effect. The data from 188 trials were standardized through parallel movement to converge the projected biomass curves [24]. The regression analysis was conducted using Proc REG of SAS 9.4 with the corn silage data of each maturity group against STP or GDD, and finally, Proc RSREG was applied to estimate the biomass response surface for the optimum response ridge (SAS/STAT ® 14.2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Test site effect within the central region were also considered as a random effect. The data from 188 trials were standardized through parallel movement to converge the projected biomass curves [24]. The regression analysis was conducted using Proc REG of SAS 9.4 with the corn silage data of each maturity group against STP or GDD, and finally, Proc RSREG was applied to estimate the biomass response surface for the optimum response ridge (SAS/STAT ® 14.2).…”
Section: Discussionmentioning
confidence: 99%
“…The response surface method was an approach to evaluate the interactive impacts of STP and GDD on corn biomass by combining those two factors at the same dimension (Figure 4), even though the impact of STP or GDD was investigated separately in the trials. As Kim et al [24] demonstrated with sorghum-sudangrass (Sorghum bicolor L.) hybrid data, the method could present the impact of STP and GDD on sorghum biomass. However, as found with the data, interactions between STP and GDD were not confirmed in early and medium-maturity corn.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the first harvest of sorghum-sudangrass hybrid in Korea is closely related to the monsoon season. Since the estimated forage production decreased after 5 days from the expected optimal harvesting time [ 24 ], the length of monsoon season determined by the frequency of heavy rainfall is also an important factor in forage production. Thus, it was recommended to seed and harvest within 5 days to secure a stable yield.…”
Section: Introductionmentioning
confidence: 99%
“…Developing a high-density genetic map is necessary for mapping quantitative trait loci (QTLs) in crops and is an essential genetic tool in other areas of molecular biology [ 13 ]. At present, domestic and foreign studies on sorghum-sudangrass hybrid mainly focus on cultivation management [ 14 , 15 ], development and utilization of the nutritional and feeding value [ 4 , 7 ], or breeding of new varieties [ 16 ], However, there are few reports on ultra-high density genetic mapping of the sorghum-sudangrass hybrid.…”
Section: Introductionmentioning
confidence: 99%